A catechol bioadhesive for rapid hemostasis and healing of traumatic internal organs and major arteries. (December 2022) - Wang, Guoqing; Meng, Xinyue; Wang, Peiyan; Wang, Xinping; Liu, Gaoli; Wang, Dong-An; Fan, Changjiang
Abstract: Uncontrolled hemorrhage caused by trauma to internal organs or major arteries poses critical threats to lives. However, rapid hemostasis followed by tissue repair remains an intractable challenge in surgery owing to the lack of ideal internal-use adhesives that can achieve fast and robust wet adhesion and accelerate wound healing. Herein, we develop a robust hemostatic bioadhesive (CAGA) from novel highly-branched aminoethyl gelatin with end-grafted abundant catechol (Gel-AE-Ca). The unique chemical structure of Gel-AE-Ca makes CAGA capable of gelling on wet tissues via synergetic cross-linking of catechol-Fe 3+ chelation and horseradish peroxidase (HRP)/H2 O2 -triggered covalent bonds using a dual-channel needle, meeting the key demands of internal medical applications (e.g., instant and strong wet adhesion, injectability, biocompatibility, self-healing, stretching flexibility, infection resistance, and proper biodegradability). It exhibits rapid gelation within 10 s and robust wet tissue adhesion up to 115.0 ± 13.1 kPa of shear strength and 245.0 ± 33.8 mm Hg of sealing strength. In vivo trials demonstrate that CAGA can not only effectively seal anastomosis of the carotid artery, but achieve rapid hemostasis on the sites of liver incisions and penetrating cardiac wounds within 10 s. The wound closure by CAGA and its timely biodegradation promote wound healing of the vital organs.